Evidence and molecular characterization of Bartonella spp. and hemoplasmas in neotropical bats in Brazil - Ikeda, P. [UNESP]; Seki, M. C.; Carrasco, A. O.T.; Rudiak, L. V.; Miranda, J. M.D.; Gonçalves, S. M.M.; Hoppe, E. G.L. [UNESP]; Albuquerque, A. C.A. [UNESP]; Teixeira, M. M.G.; Passos, C. E. [UNESP]; Werther, K. [UNESP]; Machado, R. Z. [UNESP]; et al. (Cambridge University Press (CUP), 2017)
The order Chiroptera is considered the second largest group of mammals in the world, hosting important zoonotic virus and bacteria. Bartonella and hemotropic mycoplasmas are bacteria that parasite different mammals' species, including humans, causing different clinical manifestations. The present work aimed investigating the occurrence and assessing the phylogenetic positioning of Bartonella spp. and Mycoplasma spp. in neotropical bats sampled from Brazil. Between December 2015 and April 2016, 325 blood and/or tissues samples were collected from 162 bats comprising 19 different species sampled in five states of Brazil. Out of 322 bat samples collected, while 17 (5·28%) were positive to quantitative PCR for Bartonella spp. based on nuoG gene, 45 samples (13·97%) were positive to cPCR assays for hemoplasmas based on 16S rRNA gene. While seven sequences were obtained for Bartonella (nuoG) (n = 3), gltA (n = 2), rpoB (n = 1), ftsZ (n = 1), five 16S rRNA sequences were obtained for hemoplasmas. In the phylogenetic analysis, the Bartonella sequences clustered with Bartonella genotypes detected in bats sampled in Latin America countries. All five hemoplasmas sequences clustered together as a monophyletic group by Maximum Likelihood and Bayesian Inference analyses. The present work showed the first evidence of circulation of Bartonella spp. and hemoplasmas among bats in Brazil.
Keywords: Bartonellaceae; Chiroptera; hemotrophic mycoplasmas; phylogenetic analyses; South America